A Study on Reflective Learning Model Implementation to Improve Prospective Biology Teachers’ Creativity - Efriana Jon; Asni Johari; M. Haris Effendi Hsb; Bambang Hariyadi (International Conference on Multidisciplinary Research, 2022)
Previous studies have shown that the creativity of students who are prospective biology teacher is still low. Even though some efforts have been made, the level of creativity is still low and needs to be improved. This is important before the students become teachers in the community. This study thus aims to examine the effectiveness of the reflective learning model in improving the creativity of students who are prospective biology teachers. This is a literature review study that collect references from various sources, such as journals on Google Scholar, Science Direct, Mendeley and many more to answer the research question. The results showed that the reflective learning model can improve creativity; thus, it is recommended to be applied by lecturers in teaching students who are prospective biology teachers. Keywords: learning model, reflective learning, creativity ability, prospective biology teachers.